Quality‐of‐life aspects in idiopathic epilepsy in dogs. (3rd September 2016) - Wessmann, A.; Volk, H. A.; Packer, R. M. A.; Ortega, M.; Anderson, T. J.
Abstract : Quality of life (QoL) plays a significant role in the treatment of dogs with idiopathic epilepsy (IE), yet is so far understudied. This study describes the outcome evaluation of an online questionnaire based on the carer's perception focusing on 62 QoL questions in 159 dogs with IE. Results showed that seizure frequency, but not seizure severity or presence of cluster seizures, was significantly associated with carer‐perceived dog's QoL. Dogs receiving third‐line antiepileptic drugs had a significantly lower perceived QoL than those that did not. Generalised linear mixed model analysis demonstrated that severity of the side effects sleeping more and ataxia were significantly associated with carer‐perceived dog's QoL, with higher severities predicting lower QoL scores. The degree of carer acceptability of seizure frequency and severity was significantly associated with the dog's reported seizure frequency and severity. Moreover, there was a significant association between IE‐related QoL changes of the dog and the carer, with reductions in perceived canine QoL scores associated with reductions in carer QoL, and vice versa. In conclusion, aspects of canine IE can affect both the carer and their dog's QoL. This has implications for the management and requires consideration when treatment options and outcomes are discussed.